2007
DOI: 10.1007/bf02980243
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylserine increases membrane potentials in rat C6 glioma cells

Abstract: Previously, we reported on the distinct effects of bioactive lysophospholipids, including lysophosphatidic acid (LPA), lysophosphatidylcholine (LPC), and sphingosylphosphorylcholine (SPC), on membrane potentials in rat C6 glioma cells. In the present report we have tested lysophosphatidylserine (LPS), another bioactive lysophospholipid, on membrane potentials in the same cell line. Membrane potentials were estimated by measuring the fluorescence changes of DiBAC-loaded glioma cells. LPS largely increased membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this study, the effects of wuweizisu C, gomisin A, gomisin N, and schisandrin, which are dibenzooctadiene lignans of Schisandra fruits, on the membrane potential were investigated in C6 glioma cells. We previously observed an increase of the membrane potential with sarcotride A and bio-active lysophospholipids, such as lysophosphatidic acid and lysophosphatidylserine in C6 glioma cells [29,33,34] . In the present study, we showed decreases of the membrane potential by wuweizisu C, gomisin N, and gomisin A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the effects of wuweizisu C, gomisin A, gomisin N, and schisandrin, which are dibenzooctadiene lignans of Schisandra fruits, on the membrane potential were investigated in C6 glioma cells. We previously observed an increase of the membrane potential with sarcotride A and bio-active lysophospholipids, such as lysophosphatidic acid and lysophosphatidylserine in C6 glioma cells [29,33,34] . In the present study, we showed decreases of the membrane potential by wuweizisu C, gomisin N, and gomisin A.…”
Section: Discussionmentioning
confidence: 99%
“…After 30 min of EIPA treatment, it was impossible to say whether NHE was a component of the wuweizisu C-induced decrease in the membrane potential because the resting membrane potential was decreased by the EIPA treatment. However, EIPA-sensitive NHE was definitely a regulator of the membrane potential in C6 cells [33] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation